PELATIHAN PROGRAM KECAKAPAN HIDUP BUDIDAYA IKAN LELE SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT DI PKBM LINGGIH SINAU BANYUSARI - Ali, Faisal; Hidayat, Dayat; Hoerniasih, Nia (Comm-Edu (Community Education Journal), 2024)
The phenomenon occurring in the field is that there are several village communities surrounding the Linggih Sinau Banyusari Community Learning Activity Center (PKBM) that have limited resources and lack skills in entrepreneurship, particularly catfish farming. Therefore, an effective life skills training program is necessary to enhance human resources and promote community economic empowerment. This study aims to achieve the following objectives: (1) Understand the process of life skills training at PKBM Linggih Sinau Banyusari, and (2) Determine the outcomes of catfish farming life skills training as a means of empowering the community at PKBM Linggih Sinau Banyusari. This research adopts a qualitative approach with a descriptive method and was conducted at the Center for Community Learning Activities. The research participants included six respondents, consisting of one mentor, one PKBM Chairman, and four training participants at PKBM Linggih Sinau Banyusari. Research data were collected through observation, interviews, and documentation techniques. The findings reveal that (1) participants were able to enhance their skills in entrepreneurship and cultivation by attending the life skills training program, which met their expectations and aspirations for success. The training process offered interesting activities for self-development in a conducive environment. However, participants still required encouragement and support throughout the training. (2) The outcomes of the community life skills training enabled participants to apply their newfound knowledge and bring about positive changes, particularly in their social and economic statuses.